2016
DOI: 10.17826/cutf.157335
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease: review of 21 cases

Abstract: Kawasaki disease is common in children and is an acute systemic vasculitis affecting coronary arteries. Kawasaki disease has multisystemic nature with a variety of presenting symptoms. Without treatment 20-25% of Kawasaki disease patients develop coronary artery aneurysms. Our goal is to summarize the clinical data of patients treated with Kawasaki disease at our clinics. Material and Methods: Clinical features, laboratory findings, diagnosis and treatment of 21 patients with Kawasaki disease hospitalized at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In 2 studies performed in the province of Istanbul, the diagnosis of Kawasaki disease was made most frequently during the winter and spring months. [11,12] In our study, the diagnosis of Kawasaki disease most often occurred in June. In a study performed by Topçu et al [13] in the province of Ankara, similarly, the most frequent months of Kawasaki disease diagnosis were in the winter and spring.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In 2 studies performed in the province of Istanbul, the diagnosis of Kawasaki disease was made most frequently during the winter and spring months. [11,12] In our study, the diagnosis of Kawasaki disease most often occurred in June. In a study performed by Topçu et al [13] in the province of Ankara, similarly, the most frequent months of Kawasaki disease diagnosis were in the winter and spring.…”
Section: Discussionmentioning
confidence: 75%
“…In other studies performed in our country too, leukocytosis, anemia, and thrombocytosis were observed in patients diagnosed with Kawasaki disease. [11,16,17] In cases of Kawasaki disease, the ESR and CRP values are almost always increased. In our study, the mean ESR value was 60 mm/hour, and the mean CRP was 108 mg/dL.…”
Section: Discussionmentioning
confidence: 99%